Optimalisasi Manajemen Keuangan UMKM Berbasis Prinsip Ekonomi Syariah - Mohammad Hatta Fahamsyah; Adriana Syariefur Rakhmat; Muhammad Najamuddin Dwi Miharja (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2026)
The community service activity entitled “Optimization of MSME Financial Management Based on Sharia Economic Principles” aims to enhance financial literacy and management capacity of micro, small, and medium enterprises (MSMEs) in Bekasi Regency in a sustainable manner. This program is designed to address the practical needs of business actors in managing their finances in an orderly, transparent manner and in accordance with Sharia values. Through a participatory training approach and action-based mentoring, a total of eight MSME participants took part in a series of activities, including basic financial recording training, simulations of Sharia-based financial statement preparation, as well as an introduction to various halal financing alternatives and the utilization of Sharia fintech. The results of the activity indicate a significant increase in participants’ understanding of Sharia financial concepts, rising from 45% to 85%, along with improved skills in preparing financial statements in accordance with Sharia principles. In addition, this program also generated positive social changes, marked by the establishment of the “Bekasi Berdaya Sharia MSME Group” as a platform for collective learning, business collaboration, and network strengthening. These findings demonstrate that the application of Sharia financial principles in community empowerment programs can strengthen economic resilience while fostering ethical, transparent, and value-driven business practices.